(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of the concept of "family" in linguistics, in which a comparative analysis of the study of the concept by world and Uzbek linguists as a linguocognitive and linguocultural phenomenon, the expression of the concept of family through language units in the Uzbek and English languages is carried out. The article covers the following issues: the role of the concept of "family" in language and culture, a comparative analysis of the implementation of the concept of "family" through language units (morphemes, lexemes, syntactic, phraseological and discursive units) expressing the concept of the family in the Uzbek and English languages. It also highlights the importance of the concept of family in culture, the cultural peculiarities of this concept in Uzbek and English, traditions, values and other cultural components. The role and peculiarities of the expression of the concept of family in the culture of two languages are analyzed. In conclusion, a comparative analysis of the expression of the concept of "family" through linguistic units in the Uzbek and English languages, as well as the role and features of this concept in the culture of following languages, is carried out.